Intellectual Capital Efficiency and Cost of Capital among Listed Manufacturing Companies In Nigeria - Ukpong, Mmaeyen Ofonime; Ukpong, Eno Gregory; Ibok , Nkanikpo (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
Despite the shift from industrial-based economy to knowledge-based economy, traditional accounting has continued to focus more on the physical assets in their financial statements to the exclusion of intangible asset. The main objective of this study therefore was to examine the effect of intellectual capital efficiency on cost of capital of manufacturing companies listed on the floor of the Nigerian Exchange Group from the period of 2014-2023. The research design adopted for the study was ex post facto, secondary data were used and the population of the study consisted of 62 listed manufacturing companies out of which a sample size of 27 was purposively selected. The data used in this study were analyzed using the Generalized Method of Moment (GMM) regression analysis. The findings of this study revealed that human capital efficiency (HCE), has a significant positive effect on the cost of equity; relational capital efficiency (RCE) has no significant effect on cost of equity; while structural capital efficiency (SCE) has no significant effect on cost of equity of listed manufacturing companies in Nigeria. Based on the above findings, it was concluded that intellectual capital efficiency can significantly impact on the cost of capital of listed manufacturing companies in Nigeria. It was therefore recommended among others that management of listed industrial goods companies should utilize advanced customer relationship management (CRM) systems to efficiently manage their interactions with customers and create competitive advantage.